PENGARUH KOMPETENSI, LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP PRESTASI KERJA APARATUR SIPIL NEGARA PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL BONDOWOSO - Karnadi Karnadi; Riska Ayu Pramesthi (Relawan Jurnal Indonesia, 2021)
The purpose of the study was (1) to determine the effect of the variable Competence, Work Environment, and Motivation partially or simultaneously on the variable of State Civil Apparatus Work Achievement at the Bondowoso Population and Civil Registry Service. (2) To determine the effect of the variables Competence, Work Environment and Motivation which have a dominant influence on the variable of State Civil Apparatus Work Achievement at the Population and Civil Registry Service Bondowoso. The method used in this study is the validity test, reliability test, Classical Assumption Test, multiple linear regression analysis, t test, F test and determination test. Based on the results of the study that the results of multiple linear regression are Y = -2.477E-17 + 0.456X1 + 0.444X2 + 0.395X3 + e. The results of the t-test showed that the competency variable was tcount 2.822 > ttable 2.055 sig 0.009 <0.05. Work Environment variable value tcount 2.450 > ttable 2.055 sig 0.021 <0.05. The value of the Motivation variable is tcount 2.226 > ttable 2.055 sig 0.035 <0.05, namely Ho is rejected or Ha is accepted, it can be concluded that the variables of Competence, Work Environment and Motivation partially affect work performance. The results of the F test show that the value of Fcount is 6.128 > Ftable 2.98 sig 0.003 < 0.05, that the variables Competence, Work Environment, Motivation have a simultaneous effect on Work Performance at the Bondowoso Population and Civil Registration Service. The dominant variable is Competence. R square contributes 41.4%, meaning that it has a strong enough influence on the dependent variable (Work Achievement) and the remaining 58.6% is influenced by other variables not included in the study.